Risk for progression to type 1 diabetes in first-degree relatives under 50 years of age - Urrutia, Ines; Martinez, Rosa; Calvo, Begona; Marcelo, Irene; Saso-Jimenez, Laura; Martinez de Lapiscina, Idoia; Bilbao, Jose Ramon; Castano, Luis; Rica, Itxaso, The Collaborative Working Group; Aguayo, A.; Aranaga-Decori, AC; et al. (Frontiers in Endocrinology, 2024)
The detection of pancreatic-autoantibodies in first-degree relatives of patients with type 1 diabetes (T1D) is considered a risk-factor for disease. Novel available immunotherapies to delay T1D progression highlight the importance of identifying individuals at-risk who might benefit from emerging treatments. The objective was to assess the autoimmunity in first-degree relatives of patients with T1D, estimate the time from autoimmunity detection to the onset of clinical diabetes and identify the associated risk factors.Methods: Retrospective multicenter study of 3,015 first-degree relatives of patients with T1D recruited between 1992 and 2018. Pancreatic-autoantibodies (IAA, GADA, IA2A and ZnT8A) were determined by radioimmunoassay, starting the analyses at diagnosis of the proband. All those with positive autoimmunity and normal fasting blood glucose without clinical symptoms of diabetes were followed-up in the study. Progression rate to T1D was assessed according to sex, relationship with the proband, age at autoimmunity detection, type/number of autoantibodies and HLA-DRB genotype. Cox proportional-hazard models and Kaplan-Meier survival plots were used for statistical analyses.Results: Among the relatives, 21 progenitors [43.7 years (IQR: 38.1-47.7)] and 27 siblings [7.6 years (IQR: 5.8-16.1)] had positive autoantibodies. Of these, 54.2% (95%CI: 39.2-68.6%) developed T1D (age at autoimmunity detection 11 months to 39 years) in a median of 5 years (IQR: 3.6-8.7; ranged from 0.9 to 22.6 years). Risk-factors associated with faster progression to T1D were multiple autoimmunity and < 20 years at autoimmunity detection. Younger relatives (< 20 years) with multiple autoantibodies had a 5-year cumulative risk of developing diabetes of 52.9% (95%CI: 22.1-71.6%), and a 20-year risk of 91.2% (95%CI: 50.5-98.4%). The 20-year risk decreased to 59.9% (95%CI: 21.9-79.5%) if only one risk-factor was met and to 35.7% (95%CI: 0.0-66.2%) if the relative was older than 20 years with one autoantibody.In first-degree relatives with autoimmunity, the time to progression to T1D is faster in children and adolescents with multiple autoantibodies. Young adults are also at risk, which supports their consideration in screening strategies for people at risk of developing T1D.